The new spice box: contemporary Jewish writing - Panofsky, Ruth (New Jewish Press, an imprint of University of Toronto Press, 2020)
"The New Spice Box includes short fiction, personal essays, and poetry by Jewish writers from a broad range of cultural backgrounds. Fresh and relevant, profound and lasting, this anthology features works by acclaimed short story writers David Bezmozgis, Mireille Silcoff, and Ayelet Tsabari; groundbreaking memoirists Bernice Eisenstein and Alison Pick; and award-winning poets Isa Milman, Jacob Scheier, and Adam Sol. The driving force behind The New Spice Box is the desire to uncover the twin touchstones of original expression and writerly craft, and to balance the representation of genres, styles, and authorial perspectives. Here, authors summon the past as they probe their cultural inheritance and move forward into the future. The New Spice Box shows that Jewish literary tradition, Jewish experience, and Jewish identity can be expressed in innumerable ways."--